The Construction of American National Identity Through Avant-Garde Art During the Cold War (Global Journal of Human-Social Science, 2024)
This essay explored the effect of avant-garde art on the construction of American national identity through countryadministered cultural propaganda The essay first discussed the necessity of building a national identity or image for America during that critical historical time and then demonstrated and exemplified the effectiveness of avantgarde art in achieving this goal After that the essay used artworks of Robert Rauschenberg that had been enrolled in the 1964 Venice Biennale and Rauschenberg Overseas Culture Interchange ROCI as a case study to support the above argument through visual analysis of symbols that appeared on these artworks The Cold War between America and the Soviet Union in the 20th century was a rivalry fought by two contrasting ideologies Capitalism in opposition to Socialism This intangible ideological war was reflected and visualized in political economic military social and cultural fields Prominent examples included proxy wars the Marshall Plan the Containment Policy the Space Race and the Berlin Wall et cetera In this regard this essay focused on the manifestation of one important aspect of this rivalry the construction of American national identity in avant-garde art
Keywords: avant-garde art; art history; cold war; America; national identity